Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702484
|View full text |Cite
|
Sign up to set email alerts
|

Designing Conversation Cues on a Head-Worn Display to Support Persons with Aphasia

Abstract: Symbol-based dictionaries of text, images and sound can help individuals with aphasia find the words they need, but are often seen as a last resort because they tend to replace rather than augment the user's natural speech. Through two design investigations, we explore head-worn displays as a means of providing unobtrusive, always-available, and glanceable vocabulary support. The first study used narrative storyboards as a design probe to explore the potential benefits and challenges of a head-worn approach ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
(31 reference statements)
2
21
1
1
Order By: Relevance
“…Head-worn displays have been used to provide unobtrusive, always-available, and glanceable vocabulary support to individuals with Aphasia. It was found that a head-worn approach better allows wearers to maintain focus on the conversation, reduce reliance on the availability of external tools (e.g., paper and pen) or people, and minimize visibility of the support by others [59].…”
Section: Interactive Assistive Technology For Asdmentioning
confidence: 99%
“…Head-worn displays have been used to provide unobtrusive, always-available, and glanceable vocabulary support to individuals with Aphasia. It was found that a head-worn approach better allows wearers to maintain focus on the conversation, reduce reliance on the availability of external tools (e.g., paper and pen) or people, and minimize visibility of the support by others [59].…”
Section: Interactive Assistive Technology For Asdmentioning
confidence: 99%
“…While much of the public discourse around technology and people with disabilities tend to focus on problem areas, computing has in general had a revolutionary impact on inclusiveness and access for people with cognitive, developmental, intellectual, mental, physical, and sensory impairments [CP15]. The overall term for technologies that support disabled people in daily living is assistive technologies, and they include a range of devices from low-tech, mechanical ones, such as walkers and wheelchairs, to more technologically advanced ones, such as hearing aids and Cochlear implants for people with hearing impairments, and memory aids and conversation cues [WMMF15] to support cognitive impairment.…”
Section: Assistive Technologiesmentioning
confidence: 99%
“…Diverse form factors have been explored, ranging from head-mounted devices (Hernandez, 2014), (Williams, 2015) to wristworn wearables (Ye, 2013). In terms of disciplines previously explored, existing studies were dedicated to gerontology, cardiology (Kim, 2016) and rehabilitation.…”
Section: Wearable Healthmentioning
confidence: 99%
“…In terms of disciplines previously explored, existing studies were dedicated to gerontology, cardiology (Kim, 2016) and rehabilitation. The populations benefitting from wearable applications range from patients to care givers and practitioners, from babies to older adults, and from able-bodied users to users with special needs (Ye, 2013), (Williams, 2015), (Cella et al, 2017).…”
Section: Wearable Healthmentioning
confidence: 99%